IMPLEMENTASI MANAJEMEN TENAGA KEPENDIDIKAN DI SMK TRITECH INFORMATIKA MEDAN - Rustam, Hendri Fauza, Saiful Bahri Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This study aims to determine the process of teaching staff management, starting from the planning of educational personnel, recruitment of education personnel and supervision of educational personnel at SMK Tritech Informatika Medan. In this study using a qualitative research type, namely by using a descriptive approach. In this study, the subjects of the research were the principal, vice principal (PR), the head of administration and the mathematics teacher. Techniques in data collection used are first observation then interview and finally documentation. The data analysis technique in this research is by collecting data, analyzing data, presenting the data and drawing conclusions and checking the validity of the data with credibility techniques which include Triangulation, Transferbility, dependability and confirmability. Based on the results of research and discussion, it can be concluded that the Implementation of Educational Personnel Management at SMK Tritech Informatika Medan has been going well. Planning for education personnel is carried out at SMK Tritech Informatika Medan by evaluating from the performance of teaching staff and what education personnel will be needed. Recruitment is carried out by advertising on the Job Strip, newspapers and radio, and appointments are made from two sources, namely internal and external. Supervision of education personnel has been going well with a lot of people involved, especially the head of the foundation, the principal, the vice principal of the school, administrators, external supervisors, administration and BK